Pengaruh Zakat Terhadap Indeks Pembangunan Manusia (Studi Kasus Pada BAZNAS Provinsi Bengkulu) - Amir Mukadar; Marini Marini; Katra Pramadeka (UNIVED Press, 2023)
In accordance with Law Number 23 of 2011 concerning Zakat, that the role of BAZNAS in collecting and distributing zakat is quite dominant, as an extension of the government, BAZNAS must be able to carry out its duties optimally so that the distribution of zakat can be right on target and zakat itself can have a positive effect on society especially for the mustahik This study aims to analyze the zakat utilization program carried out by BAZNAS Bengkulu Province and its impact on the life of mustahik, both in terms of changes in the post-zakat distribution of compulsory income, as well as in terms of the HDI value. By using the t-statistical calculation method, individual-level human development index (HDI), primary and secondary data were taken. The sample selection was carried out using the purposive sampling method (deliberately), which is the procedure of selecting samples based on the consideration of suitable characteristics related to the samples needed to answer the research objectives with a sample size of 150 mustahiks scattered throughout the cities and regencies in Bengkulu Province.